2020
DOI: 10.1111/cdev.13357
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Quality Effects on Learning Behavior and Later Achievement in Germany: Moderation by Socioeconomic Status

Abstract: This study investigates whether children's preschool experiences are associated with later achievement via enhanced learning behaviors using data from a German longitudinal study following children (N = 554) from age 3 in preschool to age 8 in second grade. There were two main findings. First, results suggest that more positive learning behaviors at school entry mediate effects of teacher-child interactions in preschool on second-grade achievement. Second, these effects varied by parental socioeconomic status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 68 publications
1
22
0
1
Order By: Relevance
“…Finally, the third limitation is the lack of assessment of childcare quality in the ALSPAC study. Other childcare studies have found that the quality of care was a significant factor in the association between childcare attendance and school readiness (Schmerse, 2020). Future studies need to investigate which childcare components (structural and procedural quality) and social processes (e.g., exposure to prosocial models, early cognitive stimulation, and verbalization) might explain the contribution of childcare attendance for children exposed to adversity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, the third limitation is the lack of assessment of childcare quality in the ALSPAC study. Other childcare studies have found that the quality of care was a significant factor in the association between childcare attendance and school readiness (Schmerse, 2020). Future studies need to investigate which childcare components (structural and procedural quality) and social processes (e.g., exposure to prosocial models, early cognitive stimulation, and verbalization) might explain the contribution of childcare attendance for children exposed to adversity.…”
Section: Discussionmentioning
confidence: 98%
“…For example, in comparison to those cared for at home, children from disadvantaged families who attend childcare services are better equipped to later manage classroom demands; they can show higher receptive vocabulary (Berry et al, 2016), better executive functions (i.e., inhibitory control, working memory, and attention shifting; Berry et al, 2016), and early numeracy (Dearing, McCartney, & Taylor, 2009). These compensatory effects are believed to unfold via the provision of age‐appropriate learning materials and activities to stimulate language acquisition, early socialization, and the development of executive functions (McCartney, Dearing, Taylor, & Bub, 2007; Schmerse, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Task persistence has been associated with teacher reports of students' academic competencies as well as student social and self-regulation skills (Berhenke et al, 2011;Fantuzzo et al, 2005;Li-Grining et al, 2010). Specifically, ratings of student persistence have been linked to behavioral assessments of cognitive control (Sasser et al, 2015;Sung & Wickrama, 2018;Vitiello & Greenfield, 2017), the acquisition of early reading and math skills (Newman et al, 1998;Schmerse, 2020), and achievement trajectories in math and reading across elementary school (Li-Grining et al, 2010).…”
Section: Task Persistencementioning
confidence: 99%
“…Much of the research on persistence is based on global parent or teacher reports of children's engagement in the classroom or with homework materials (Schmerse, 2020;Sung & Wickrama, 2018;Vitiello et al, 2011;Vitiello & Greenfield, 2017). However, learning-related behaviors are thought to be context or task-specific (Barrett & Morgan, 2018;.…”
Section: Task Persistencementioning
confidence: 99%
“…The learning processes supported by online technology and data technology ensure the completeness and continuity of learning behavior data. Massive learning behaviors is an important part of education big data, which provides the possibility for the full development of learning analytics [3,4]. Learning behavior data can be divided into two categories: horizontal format and vertical format from the perspective of data structure and feature attributes.…”
Section: Introductionmentioning
confidence: 99%